Analysis Of Homosexual Representation In I Am Gay Videos Semiotika Studies - Safira Siti Nadhilah Hanif (Publikasi Indonesia, 2023)
Social media is currently one of the most effective platforms for self-expression. The media currently in demand as a forum for this expression is YouTube. YouTube is a social media that uses video as the primary medium for distributing content. In addition to conveying information, YouTube can be used for self-expression, one of which is in the coming out process for the LGBTQ+ group. This coming out process was found in the LGBTQ+ group, who began to openly state that they belonged to the group and accepted their identity. One of the coming-out videos that has had a considerable impact over the last few years is I am Gay by Eugene Lee Yang. This study will evaluate the representation of homosexuals in the modern media of YouTube and analyze it from a semiotic perspective, namely the meaning of connotations, denotations, and myths listed.